Values of Caring and Knowing: A case of Malaria - Gitonga, Pius; Mwamisi, Joseph; Gatere, Ruth (My University, 2016)
Health care is a universal right for all human beings; individuals or families or communities. Care is a universal need for all humans. The relationship between caring and knowing is complex and involves a constant reflective process of professional training. Caring involves displaying kindness and concern for others while knowing is the state of being aware or informed. In fact, people do not care how much we know until they know how much we care about them. Knowledge of self-worth creates value for others, their pain, the standards of care and processes to alleviate pain, suffering and patient’s perspectives and dimensions of pain, care and healing. Caring takes a very strong, intelligent, and compassionate person to take on the tasks of caring with passion and purpose to maintain the health and well-being of the human person. Anecdotes suggest that even those without diseases require some degree of care and love. In many occasions, whenever pain comes our way, we desire to be healed from the obnoxious feeling. During the healing process, care is given by family members or health care professionals; knowing how to take care for the suffering is a professional preparation and the proximity to those in needs by their significant others and family members plays a pivotal role in the healing process. The sick should also be willing to be optimistic in the healing process. The family members and significant others need to know that taking care of the sick and weak is more demanding than taking care for the well and healthy. Caring to know the other person’s pain and caring to know what causes it and how to relieve or remove it, is important knowledge as we purpose to heal the human person through diagnosis, planning and implementing treatment regimens and discuss about integrated care protocols. Medical and nursing knowledge helps make our caring acts more productive and fruitful. Knowing and caring is our drive and our avenue to show empathy to sick, healthy, recovering or deteriorating from illnesses and diseases
Keywords: Empathy; Caring; Knowing; healing; nursing care; family nursing